2009
DOI: 10.4049/jimmunol.0804002
|View full text |Cite
|
Sign up to set email alerts
|

Defective Regulatory T Cells In Patients with Severe Drug Eruptions: Timing of the Dysfunction Is Associated with the Pathological Phenotype and Outcome

Abstract: Toxic epidermal necrolysis (TEN) and drug-induced hypersensitivity syndrome (DIHS) represent two ends of a spectrum of severe drug eruptions: DIHS is unique in that severe epidermal damage seen in TEN is absent, sequential reactivations of herpesviruses occur, and autoimmunity often ensues. To investigate whether changes in regulatory T (Treg) cell function would contribute to variability in the clinical manifestations, we examined the frequency, phenotype, and function of Treg cells both during the acute stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
203
3
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(234 citation statements)
references
References 49 publications
12
203
3
6
Order By: Relevance
“…Another possible mechanism for the induction of TEN by MOG is depletion by MOG of CCR4 positive regulatory T cells, which is reported previously [8]. Takahashi et al reported that a transitory impairment in the function of regulatory T cells during the acute stage of TEN may be related to severe epidermal damage [9].…”
Section: To the Editormentioning
confidence: 63%
“…Another possible mechanism for the induction of TEN by MOG is depletion by MOG of CCR4 positive regulatory T cells, which is reported previously [8]. Takahashi et al reported that a transitory impairment in the function of regulatory T cells during the acute stage of TEN may be related to severe epidermal damage [9].…”
Section: To the Editormentioning
confidence: 63%
“…Although multiple allergy to drugs was first reported more than 20 years ago [19,20], studies to elucidate the mechanism have been carried out only for T cell-dependent reactions, where sensitization to multiple drugs could occur both simultaneously and sequentially [19][20][21]. An imbalance of the immune system caused by effector and/or regulatory T cells may be involved [24,33].…”
Section: Discussionmentioning
confidence: 99%
“…Foxp3 + Tregs were shown to expand quickly during the course of immune reconstitution; thus, these expanded Tregs could act to prevent lymphopenia-associated autoimmunity in individuals recovering from lymphopenia in mice (29). Importantly, similar expansions of fully functional Tregs during the acute phase and the subsequent contraction upon resolution of disease as observed in EH also were reported to occur in patients with sarcoidosis or drug-induced hypersensitivity syndrome (30,31), both of which fit within the spectrum of immune reconstitution syndrome (32,33). In a recent retrospective analysis (1) of 100 cases of EH, 36% of the patients had noted a severe exacerbation of their AD that typically had started ∼2 wk before the onset of EH, and the majority of the patients had not received any corticosteroid therapy in the 4 wk before the onset of EH.…”
Section: Hsv-specific Cd4mentioning
confidence: 66%